Stability of flexible orbital structures - Andra-Ana-Maria GHEORGHIU; Cristian-Emil CONSTANTINESCU (INCAS Bulletin)
This paper presents the study of the stability of flexible orbital structures. The stability of the motion of space tether systems is analysed using methods that include mathematical models for solving equations. The selection of material for performing the simulations was important in order to reproduce the conditions in the Earth orbit as precisely as possible. A long cable configuration of space tether was analysed in the simulations. Comparisons between the structures were made, for various values of the elasticity and damping constants. Finally, an optimal configuration was chosen according to dynamic stability and endurance in the space environment.